The Existence of Marriage Dispensation After the Revision of the Marriage Law at the Religious Court of Donggala, Central Sulawesi - Abidin Abidin; Sudirman B.; Marzuki Marzuki (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2022)
The Indonesian government regulates the age of marriage through Law Number 16 of 2019. This rule states that the minimum age for marriage is 19 years. Nevertheless, marriage dispensation given by the government is often used as a loophole for deviation and legalization of child marriage. This study describes this phenomenon after the revision of the Law on Marriage, the factors, and impacts of the dispensation based on judicial practice at the Religious Courts in Donggala Regency. The examination uses a socio-juridical model with theological-normative, juridical-normative, and legal sociology approaches. The data were collected by interview, documentation, and observation methods. The analysis was carried out using reduction techniques, data presentation, and conclusion formulation. The dispensation of marriage caused by the disharmony of regulations and the contradictory nature between the Marriage Law and the Child Protection Act results in weak law enforcement and minimal compliance with it from the community. Multi-factor considerations, including religion, social, culture, economy, education, health, and other factors, are often considered in giving marriage dispensation.